The influence of motivation on the activeness of elderly people with hypertension in prolanis gymnastics activities - Anggeraeni Anggeraeni; Nur Asiah; Anita Lontaan; Asridawati Akib; Cipto Susilo (Edukasi Ilmiah Indonesia, 2024)
Introduction: Population ageing is one of the significant challenges in modern society, with the increasing number of elderly populations. Prevention and management of health conditions have become very important, and the Prolanis gymnastics program has been recognized as one of the effective methods. Motivation plays a central role in shaping health behaviours and habits. Methods: This research is quantitative with an analytical design with a sectional study design approach. The population in this study was all Prolanis Participants suffering from Hypertension, with the number of samples in the survey 41 respondents. The sampling technique used in this study was accidental sampling. Results: The Chi-square Statistical test on the influence of motivation on the participation of older adults with Hypertension in prolonged gymnastics activities obtained a p-value = 0.000 or smaller than a = 0.05 (0.000<0.05). Conclusions: The influence of motivation on the activeness of older adults with Hypertension in protagonist gymnastics activities. Motivation influences the activeness of older adults with Hypertension in prolantic gymnastics activities. High motivation can be an essential factor in encouraging active participation in prolanist gymnastics programs, which in turn can support the management of hypertensive conditions and improve the well-being of older people. However, it is essential to remember that these conclusions are general and cannot be taken as absolute truth without supporting data and evidence.